2012
DOI: 10.1021/la205036p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Science of DNA Adsorption onto Citrate-Capped Gold Nanoparticles

Abstract: Single-stranded DNA can be adsorbed by citrate capped gold nanoparticles (AuNPs), resulting in increased AuNP stability, which forms the basis of a number of biochemical and analytical applications, but the fundamental interaction of this adsorption reaction remains unclear. In this study, we measured DNA adsorption kinetics, capacity, and isotherms, demonstrating that the adsorption process is governed by electrostatic forces. The charge repulsion among DNA strands and between DNA and AuNPs can be reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
311
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 282 publications
(331 citation statements)
references
References 62 publications
15
311
1
4
Order By: Relevance
“…22,[24][25][26] The adsorption of non-thiolated DNA has also found important applications in analytical chemistry, [27][28][29][30][31][32][33][34] polymerase chain reactions, 35,36 nanoparticle synthesis, 37,38 and medicine. 37,39 We recently reported that at neutral pH, each 13 nm AuNP adsorbs just around twenty 12-mer DNAs even after overnight incubation, 40 which is consistent with the results from the literature using polyadenosine (e.g A20) as an anchoring block for DNA adsorption with the salt aging approach. 41 This number is much lower than that can be achieved using thiolated DNA (up to 130 DNAs on each 13 nm AuNP), supporting the DNA wrapping model presented in Figure 1B.…”
Section: This Document Is the Accepted Manuscript Version Of A Publissupporting
confidence: 87%
See 1 more Smart Citation
“…22,[24][25][26] The adsorption of non-thiolated DNA has also found important applications in analytical chemistry, [27][28][29][30][31][32][33][34] polymerase chain reactions, 35,36 nanoparticle synthesis, 37,38 and medicine. 37,39 We recently reported that at neutral pH, each 13 nm AuNP adsorbs just around twenty 12-mer DNAs even after overnight incubation, 40 which is consistent with the results from the literature using polyadenosine (e.g A20) as an anchoring block for DNA adsorption with the salt aging approach. 41 This number is much lower than that can be achieved using thiolated DNA (up to 130 DNAs on each 13 nm AuNP), supporting the DNA wrapping model presented in Figure 1B.…”
Section: This Document Is the Accepted Manuscript Version Of A Publissupporting
confidence: 87%
“…Cytosine (pKa = 4.2) and adenine (pKa = 3.5) can be effectively protonated at pH 3, thus decreasing the electrostatic repulsion and favoring DNA adsorption onto AuNP surfaces. The loading of FAM-T15 at pH 3 was similar to that achieved at neutral pH, 40 consistent with the fact that thymine cannot be protonated at pH 3. A 12-mer DNA with random sequence (Table 1) also showed a high loading capacity of ~93 DNA per AuNP at pH 3 ( Figure 2B).…”
Section: Based Onsupporting
confidence: 76%
“…For metallic nanoparticles (e.g., AuNPs) and carbon-based nanomaterials (e.g., graphene oxide and carbon nanotubes), DNA adsorption is achieved mainly via base interaction. [8][9][39][40][41] For example, adding phosphate has little effect on DNA adsorbed by these materials. Many MONPs (e.g., TiO2, CeO2, ITO) adsorb DNA mainly via the phosphate 10 backbone.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22] We reason that this problem might be overcome by introducing more specific intermolecular forces based on the properties of the target molecules. For this purpose, DNA is an ideal model target to obtain fundamental insights since arbitrary sequences and modifications are readily accessible through chemical DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, citrate-capped gold nanoparticles (AuNPs) strongly bind to DNA bases. [18][19][20][21][22] Negatively charged graphene oxide (GO) adsorbs DNA via hydrophobic interactions, hydrogen bonding and π-π stacking. [23][24][25] In both cases, ss-DNA adsorbs much faster than ds-DNA.…”
Section: Introductionmentioning
confidence: 99%